2006
DOI: 10.1002/jcp.20908
|View full text |Cite
|
Sign up to set email alerts
|

PECAM‐1 modulates thrombin‐induced tissue factor expression on endothelial cells

Abstract: Platelet endothelial cell adhesion molecule-1 (PECAM-1) (CD31) is known to inhibit platelet function and thrombus formation. The mechanisms involved in PECAM-1's roles as a modulator of hemostasis are still not completely understood. We examined the role of PECAM-1 as a regulator of tissue factor (TF) expression, a known important inducer of thrombosis. Wildtype and CD31KO mice underwent transient (30 min) renal ischemia followed by 24 h re-perfusion and their kidneys assessed for apoptosis, fibrin formation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 55 publications
3
36
1
Order By: Relevance
“…These findings support the concept that CD44 mediates several of its effects in endothelia through modulation of cell junctional molecule expression (e.g. CD31 and VE-cadherin), which, in addition to its known modulation of junctional integrity, matrix metalloproteinase levels and activation, interactions with cortical membrane proteins, and selected signaling pathways, modulates proliferation and apoptosis (22)(23)(24)(25)(26)(27)(28)(29), further defining the integrated roles of CD44, VE-cadherin, and CD31 as critical regulators of vascular function.…”
supporting
confidence: 74%
“…These findings support the concept that CD44 mediates several of its effects in endothelia through modulation of cell junctional molecule expression (e.g. CD31 and VE-cadherin), which, in addition to its known modulation of junctional integrity, matrix metalloproteinase levels and activation, interactions with cortical membrane proteins, and selected signaling pathways, modulates proliferation and apoptosis (22)(23)(24)(25)(26)(27)(28)(29), further defining the integrated roles of CD44, VE-cadherin, and CD31 as critical regulators of vascular function.…”
supporting
confidence: 74%
“…PECAM‐1 has been shown to have proinflammatory activity through the promotion of leukocyte‐endothelial translocation and transmission of systemic signals associated with endothelial stress 37. Unlike platelet P‐selectin, which supports neutrophil‐platelet and platelet‐endothelial interactions, platelet PECAM is an inhibitory molecule that has been proposed to limit thrombus formation by limiting platelet‐platelet interactions as well as platelet adhesion to collagen 34, 38, 39. These studies have suggested that PECAM‐1 serves to regulate thrombus formation and thereby inhibit vessel occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…The above mentioned mediators stimulate, after binding to their corresponding receptor, the MAP kinases p38, ERK, and c-jun terminal NH2-kinase with downstream activation of transcription factors such as NFκB, AP-1 or EGR-1. [20][21][22] Also the protein kinase C as well as the Rho-Kinase pathway 17,23 are known to mediate TF induction. In contrast, the PI3 kinase pathway and its downstream target Akt, GSK-3β, and the mammalian target of rapamycin inhibit TF expression either at the transcriptional or the translational level.…”
Section: Molecular Structure and Distribution Of Tfmentioning
confidence: 99%